Climate Weirding and Queering Nature: Getting Beyond the Anthropocene - Whitney A. Bauman (Religions, 2015)
Though many scientists and scholars of the environmental humanities are referring to the current geological era as the anthropocene, this article argues that there are some problems with this trope and the narrative that emerges from it. First, responsibility for the current era of climate weirding is not shared equally, some humans are way more responsible than others. Second, the claim of the anthropocene works rhetorically to maintain a sense of human exceptionalism from the rest of the evolution of life on the planet. Third and finally, the suggestion that this geological era be named the anthropocene suggests that the problem and the solution to our ecological crisis lie with Homo sapiens. Does this not re-create the sense of mastery that has fueled contemporary planetary ills in the first place? This paper argues that the idea of agency must be reconfigured and redistributed throughout the planetary community in order to deal with the wicked problems arising from climate weirding and an uncertain future.